A continuous-flow synthesis of primary amides from hydrolysis of nitriles using hydrogen peroxide as oxidant. Issue 13 (29th March 2018) - Zhan, Wei; Ji, Ling; Ge, Ze-mei; Wang, Xin; Li, Run-tao
Abstract: A continuous-flow synthesis of primary amides from hydrolysis of nitriles using hydrogen peroxide as oxidant has been developed. Using this procedure, a variety of nitriles could be smoothly transformed into the desired primary amides in good to excellent yields. The mild reaction conditions and the flowing reaction system greatly improved the safety and make the reaction easy to scale up. Graphical abstract: